The association between altered lipid profile and suicide attempt among Tunisian patients with schizophrenia. Issue 1 (December 2016) - Mensi, Rym; Messaoud, Amal; Mhallah, Ahmed; Azizi, Islem; Salah, Walid; Douki, Wahiba; Najjar, Mohamed; Gaha, Lotfi
Abstract Background There have been many studies on psychiatric disorders, but very little is known about the biology of suicide with schizophrenia. In the present study, we are looking for a possible connection between altered lipid profile and suicidal behavior in schizophrenic Tunisian patients. Methods Assay of total cholesterol (TC), high-density lipoprotein cholesterol (HDL-c), low-density lipoprotein cholesterol (LDL-c), and triglycerides (TG) has been done for 126 schizophrenic patients with and without suicide attempts and 131 healthy controls recruited in the University Hospital of Monastir. Results TC and LDL-c levels were significantly higher in schizophrenic patients compared to controls. TC was significantly lower in schizophrenic patients with suicide attempt compared to those without suicide attempt. Depending to the sonority of suicide attempt, TC was significantly lower in patients with recent suicide attempt compared to those with lifetime suicide attempt and without suicide attempt (p  < 0.001), and no significant differences between TG, LDL-c, and HDL-c were noted. Conclusions Results of this study showed that TC levels in schizophrenic patients after a recent suicide attempt are significantly lower than in patients without suicide attempt and with lifetime suicide attempts. TC can be one of biological markers defined suicidal risk for schizophrenic patients.